2021
DOI: 10.1007/s42461-021-00506-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Working Conditions and Opinions of Mine Workers When Battery Electric Vehicles (BEVs) Are Used Instead of Diesel Machines — Results of Field Trial at the Kittilä Mine, Finland

Abstract: A major part of the European Union’s (EU) project Sustainable Intelligent Mining System (SIMS) is investigating the development of diesel-free/carbon–neutral underground mines in order to ensure sustainable underground mining in the future. Replacing diesel machines with electric vehicles in underground hard rock mines has been widely acknowledged by the mining industry worldwide as a critical step to improve working conditions by reducing diesel exhaust–related contaminants, to reduce mine ventilation electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Their results indicated that the energy consumption of overhead catenary trucks was comparable to battery-electric trucks and significantly lower than that of conventional diesel trucks. In the Sustainable Intelligent Mining System (SIMS) project, a field BEVs' trial was discussed in Halim, et al (2022) [14], which demonstrated that using BEVs improved working conditions in terms of reduced emissions, Diesel Particulate Matter (DPM), and noise, as perceived by mine workers surveyed during the trial. Mazumdar (2011) presented the performance improvement of trolley-assisted haul trucks through simulation studies and field experimental results [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results indicated that the energy consumption of overhead catenary trucks was comparable to battery-electric trucks and significantly lower than that of conventional diesel trucks. In the Sustainable Intelligent Mining System (SIMS) project, a field BEVs' trial was discussed in Halim, et al (2022) [14], which demonstrated that using BEVs improved working conditions in terms of reduced emissions, Diesel Particulate Matter (DPM), and noise, as perceived by mine workers surveyed during the trial. Mazumdar (2011) presented the performance improvement of trolley-assisted haul trucks through simulation studies and field experimental results [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The socioeconomic aspects are reflected not only in extensive measures to include and interact with the public to reshape the perception of mining but also in the concept of the “digital miner” that was developed as part of the preceding SIMS project and is being further elaborated in the NEXGEN SIMS project. The question of what the future workplace will look like and how digitalisation will impact the workplace from a worker’s perspective is central to the concept of the digital miner (Lööw and Johansson 2020 ; Halim et al 2021 ; Lööw et al 2019 ).…”
Section: Technological Dimensions Of Changementioning
confidence: 99%
“…With respect to technology development, however, there is another factor, which is the necessity to consider the impact of technology from a workplace perspective from the onset. An often neglected part of technology development is the necessity to include a perspective on human factors, “the human side of mining”, and potential implications, negative or positive, that digitalisation and automation may have, in order to shape the kind of impact technology will have on the operation but also on the workers in particular (Lööw et al 2019 ; Lynas 2011 ; Lööw and Johansson 2020 ; Halim et al 2021 ). As Lööw et al state, “used correctly, digitalisation can create attractive jobs in safe control room environments, which provide space for the employee’s full expertise and creativity […] but, to succeed […] we must also consider the risks, such as privacy issues, increased stress, and work-life boundaries” (Lööw et al 2019 ).…”
Section: Non-technological Dimensions Of Changementioning
confidence: 99%
See 1 more Smart Citation
“…Mining lithium-ion batteries (MLIBs) have emerged, meeting the practical needs for safe production, energy conservation, and emission reduction. 1 Consequently, MLIB has been widely adopted in various mining equipment, such as electric mining trucks, 2 electric auxiliary transportation equipment, and backup power supplies for mining applications. 3 This trend has not only propelled the mining industry towards a greener, more efficient, more intelligent direction but also underscored the pivotal role of MLIB in the high-quality development of coal mines.…”
mentioning
confidence: 99%